Understanding the multi-dimensional nature of cultural identity in historic urban landscapes: a study of Jiaxiulou in Guiyang, China - Linfeng, Shi; Wanyi, Yang; Ujang, Norsidah (Bucharest University Press, 2024)
The conservation and sustainable development of historic urban landscapes (HUL) are imperative in the face of rapid urbanisation. This study, based on Jiaxiulou in Guiyang City, China, examines the dimensions of cultural identity (CI) in HUL. Using a mixed qualitative and quantitative approach, a three-dimensional model of CI is validated, comprising cognitive, emotional, and behavioural aspects. Results show that while cognitive understanding of HUL is essential, it alone does not directly influence the residents' emotions and behaviours. Pride in cultural heritage emerges as a significant driver of CI, impacting the residents' perceptions and behaviours. Conversation behaviour is identified as a primary expression of CI. Recommendations are proposed to integrate local values into urban planning, to enhance public participation, and to provide diverse cultural activities for the residents, highlighting the importance of social engagement in shaping CI. This study contributes to understanding the complexity of CI and its role in HUL conservation and sustainable development.